Pengaruh Dukungan Sosial dan Stigma Masyarakat Terhadap Beban Keluarga Pasien Jiwa - Suara, Mahyar; Khasanah, Siti (Universitas Malahayati, 2025)
ABSTRACT WHO in 2023 almost 1 billion people in the world live with mental health conditions, and approximately 21% of adults in the United States experience mental illness. The prevalence of mental disorders in Indonesia in 2023 is 0.73% of the total population, or around 2,023,009 people. Of the 34 provinces that reported, 8 provinces achieved above 100%, namely Aceh, Riau Islands, Jambi, Bengkulu, Kep. Bangka Belitung. Negative stigma by the environment towards mental disorders patients not only causes the patient to be isolated from the environment, but also becomes a psychological burden for their families. To determine the influence of social support and community stigma on the burden on families of mental patients. Analytical with cross sectional design. The samples in this study were some of the families of mental patients who visited the hospital. Duren Sawit in January 2025, with a sample size of 50 people. The sampling technique uses random sampling. The frequency distribution of the burden on families of mental patients is mostly moderate (48.0%), social support is lacking (42.0%) and societal stigma is moderate (44.0%). There is an influence of social support on the burden on families of mental patients at Duren Sawit Hospital (p. value 0.002). There is an influence of community stigma on the burden on families of mental patients at Duren Sawit Hospital (p. value 0.001). There is an influence of social support and community stigma on the burden on families of mental patients. It is hoped that the hospital will further improve health services, especially for families of mental patients, by providing education about the care of mental patients on a regular basis so that it can minimize the family stigma towards schizophrenic patients. Keywords: Social Support, Community Stigma, Family, Mental Patients ABSTRAK WHO tahun 2023 hampir 1 miliar orang di dunia hidup dengan kondisi kesehatan mental, dan sekitar 21% orang dewasa di Amerika Serikat mengalami penyakit mental. Prevalensi gangguan jiwa di Indonesia pada tahun 2023 adalah 0,73% dari total penduduk, atau sekitar 2.023.009 jiwa. Dari 34 provinsi yang melaporkan, capaian yang diatas 100% sebanyak 8 provinsi yaitu Provinsi Aceh, Kepri, Jambi, Bengkulu, Kep. Bangka Belitung. Stigma negatif oleh lingkungan terhadap pasien gangguan jiwa tidak hanya menyebabkan terkucilkannya pasien dari lingkungan, tetapi menjadi beban psikologis bagi keluarganya. Mengetahui pengaruh dukungan sosial dan stigma masyarakat terhadap beban keluarga pasien jiwa. Analitik dengan rancangan cross sectional. Sampel dalam penelitian ini adalah sebagian keluarga pasien jiwa yang berkunjung di RS. Duren Sawit pada bulan Januari 2025, dengan jumlah sampel sejumlah 50 orang.Teknik pengambilan sampel menggunakan randoom sampling. Distribusi frekuensi beban keluarga pasien jiwa mayoritas sedang (48,0%), dukungan sosial kurang (42,0%) dan stigma masyarakat sedang (44,0%). Ada pengaruh dukungan sosial terhadap beban keluarga pasien jiwa di Rumah Sakit Duren Sawit (p. value 0,002). Ada pengaruh stigma masyarakat terhadap beban keluarga pasien jiwa di Rumah Sakit Duren Sawit (p. value 0,001). Ada pengaruh dukungan sosial dan stigma masyarakat terhadap beban keluarga pasien jiwa. Diharapkan Rumah Sakit lebih meningkatkan pelayanan kesehatan khususnya untuk keluarga pasien jiwa dengan memberikan penyuluhan tentang perawatan pasien jiwa secara rutin sehingga bisa meminimalisir adanya stigma keluarga terhadap pasien skizofrenia. Kata Kunci: Dukungan Sosial, Stigma Masyarakat, Keluarga, Pasien Jiwa